2017
DOI: 10.1159/000484925
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Haemodialysis Therapy of Chronic Haemodialysis Patients Prevents Calcification and Apoptosis of Vascular Smooth Muscle Cells in vitro

Abstract: Background: Vascular calcification is a common phenomenon in patients with chronic kidney disease and strongly associated with increased cardiovascular mortality. Vascular calcification is an active process mediated in part by inflammatory processes in vascular smooth muscle cells (VSMC). These could be modified by the insufficient removal of proinflammatory cytokines through conventional high-flux (HF) membranes. Recent trials demonstrated a reduction of inflammation in VSMC by use of dialysis membranes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…The next question to answer will be: is this clearance of medium molecules achieved with HDx associated with better patient outcomes? The answer seems to be yes, as suggested by a recently study published by Willy et al [23]. This study shows that HDx reduces the vascular calcifications in chronic HD patients.…”
Section: Discussionmentioning
confidence: 60%
“…The next question to answer will be: is this clearance of medium molecules achieved with HDx associated with better patient outcomes? The answer seems to be yes, as suggested by a recently study published by Willy et al [23]. This study shows that HDx reduces the vascular calcifications in chronic HD patients.…”
Section: Discussionmentioning
confidence: 60%
“…There are no comparative studies on glomerular filtration with respect to the size of the four molecules of VKDPs. However, two studies tested filtration through dialysis membranes, but only MGP was assessed among the four VKDPs [29,30]. Both studies observed that, after incubation with conventional HF serum, VSMCs produced significantly higher concentrations of MGP than VSMCs under HCO, MCO and HRO serums.…”
Section: Discussionmentioning
confidence: 99%
“…The process of identification, selection, screening and inclusion of the studies are depicted in Figure 1. The following studies were included: MGP [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]; OC [9,10,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]; Gas6 [70,71,72,73,74,75,76,77,78,79,80,8...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies have demonstrated potential clinical benefits of MCO membranes in reducing cardiovascular risk by reduction of vascular calcification [29] and by decreasing the inflammatory allostatic load associated with retention of middle molecular weight uremic toxins [30]. With the potential of better removal of larger middle molecules, HDX may improve pruritus and restless legs syndrome [31].…”
Section: Expanded Haemodialysis (Hdx): An Emerging Alternative To Higmentioning
confidence: 99%